INDEPENDENSI MEDIA DALAM PEMBERITAAN REUNI AKSI 212 TAHUN 2018: STUDI FENOMENOLOGI REDAKSI KORAN LOKAL RADAR BANYUMAS - Fajar Kurniawan, Yudhis (Jurnal El-Hamra : Kependidikan dan Kemasyarakatan, 2019)
Media independence determines the choice of news published by the media. This was the background of the research on the Reuni Aksi Damai 212 of the 2018 , which not all media reported. Editorial Radar Banyumas is a main division of independence in the news of Reuni Aksi 212 of 2018. The purpose of this research is to find out the meaning of Editorial Radar Banyumas about independence, knowing the views of Editorial Radar Banyumas about independence in the Reuni Aksi Damai 212. This research based on Alfred Schutz's theory of phenomenology with data collection techniques through observing news of Reuni Aksi Damai of 212 in the Radar Banyumas Newspaper, in- depth interviews with related personels, literature studies and documentation studies.The approach used in this study is a descriptive qualitative approach. The results of this research showed that Radar Banyumas as one of the most popular in Banjarnegara Regency, Purbalingga, Banyumas, Cilacap and Kebumen, maintained independence inreporting. Independence becomes an important thing in carrying out the profession as an editorial crew. This is so that editors can maintain the objectivity and balance in publishing news. Editor in Chief Radar Banyumas in publishing the news of the Reuni Aksi Damai 212 to maintain independence by relying on news value.Key Word: Independece, Editor, Radar Banyumas, Reuni Aksi 212